Prevalence and risk factors of high blood pressure among persons assessed for TB at three health facilities in Lusaka, Zambia - Muzazu, Seke G. Y.; Siameka, Daniel; Sanjase, Nsala; Shuma, Brian; Kagujje, Mary; Muyoyeta, Monde (Frontiers in Tuberculosis, 2025)
BackgroundLow- and middle-income countries (LMICs) are experiencing a rapidly increasing burden of non-communicable diseases (NCDs), additionally straining health systems battling with high prevalence of infectious diseases such as tuberculosis (TB). This study set out to describe the prevalence of a high blood pressure (HBP) and identify factors associated with high BP among persons with presumed and diagnosed TB patients in a high TB burden setting.MethodsWe conducted secondary analysis of data from a cross-sectional study that enrolled consecutive persons with presumed TB and those at high risk for TB, aged ≥18 years old, between November 2021 and December 2022 in Lusaka, Zambia. We defined a high blood pressure (HBP) reading as any systolic ≥140 mmHg and/or diastolic ≥90 mmHg. Descriptive statistics were employed to summarize participant demographic and clinical characteristics while logistical regression analysis was used to identify factors associated with HBP.ResultsOf 2,431 participants, 541 (26.9%) had HBP and 290 (11.9%) had bacteriologically confirmed TB. Among those with HBP, 51/541 (7.8%) had TB. Overall, 1,305 (53.6%) were female, median age was 35 years (IQR = 27–45), 899 (36.9%) were living with HIV, 383 (15.7%) were overweight, and 209 (8.6%) were obese. We noted a history of tobacco use among 718 (29.5%), and 1,078 (44.3%) reported alcohol use during the past year. The odds of a high BP increased with ages 35–44 (aOR = 1.57, 95%CI = 1.22–2.02); 45–54 (aOR = 2.10, 95%CI = 1.59–2.76); and over 55 (aOR = 4.30, 95%CI = 3.11–5.95) years, alcohol use (aOR = 1.40, 95%CI = 1.15–1.71), and BMI over 30 (aOR = 1.64, 95%CI = 1.20–2.25). Conversely, participants with bacteriologically confirmed TB (aOR = 0.63, 95%CI = 0.45–0.88), aged 18–24 years (aOR = 0.58, 95%CI = 0.41–0.82), and BMI <18.5 (aOR = 0.62, 95%CI = 0.47–0.80) had lower odds of HBP.ConclusionOver 1 in 4 persons assessed for TB had HBP on initial reading. Higher BMI, alcohol use and older age were associated with increased HBP prevalence. These results provide valuable baseline data to inform strategies for integrated TB and non-communicable diseases (NCDs) including HBP screening in similar settings.